POTENTIAL CONFLICT OF LAND DEED IN THE PERSPECTIVE OF NOTARY POSITION - I Made Pria Dharsana; I Nyoman Sumardika; Putu Ayu Sriasih Wesna; I Wayan Wesna Astara (NOTARIIL Jurnal Kenotariatan, 2021)
This study aims to find out the potential conflicts on Land Deeds made by Notaries and to find out Notary efforts in making Land Deeds to minimize potential land conflicts. The method used in this study is the normative legal research method. In addition, the statute approach, conceptual approach, and analytical approach are the approach used in this study. The results of this study showed that (1) potential conflicts on Land Deeds made by Notaries are due to Notaries in carrying out their positions tend to be in a dilemma which on the one hand must comply with legal provisions with a normative nature, and on the other hand, empirical facts are so complex and often cannot be handled and accommodated by regulations that tend to be rigid. This is because when carrying out its positions, the Notary must serve the client, while the client needs service without being too concerned with the regulations that bind the Notary. (2) Notary efforts in issuing Land Deeds to minimize the potential for Land Conflicts are required to examine the completeness of documents by applying the precautionary principle to protect the real owner and reduce conflicts in the land sector. The application of the precautionary principle of the Notary in producing the PPJB deed and the Lease Agreement deed to registered land rights to be registered at the Land Office must start from the stage before the deed, the stage at which the deed is made and the reading of the deed.